Developing sustainable digital libraries : socio-technical perspectives - Ashraf, Tariq, 1961-; Sharma, Jaideep; Gulati, Puja Anand, 1978- (Information Science Reference, 2010)
"This book provides tools to complement an organization's burgeoning information treasuries, exploring new frontiers by looking at social and economic aspects of digital libraries and their sustainability"--Provided by publisher.